THE ROLE OF INNOVATION IN THE FIELD OF SERVICE PROVISION (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
The role of innovation in the service sector, the importance of an innovative approach is revealed in the article. The characteristics of the types of innovations in the service sector were considered, the main criteria of innovations in the service sector were proposed. Proposals for effective organization of innovative processes in the Republic of Uzbekistan are given.